Time course of changes in straddle jump and vertical jump performance after acute static stretching in artistic gymnasts - Köse, D. E.; Aksit, T.; Açikgöz, O.; Ceyhan, G. (Science of Gymnastics Journal, 2023)
The aim of the present study was to examine the time course of changes of the effects of static stretching on straddle jump, vertical jump height and flexibility after performing dynamic movements in artistic gymnasts. The study was participated by 14 female artistic gymnasts aged between 9 and 14. Vertical jump heights were measured using the New Test 2000 testing device. Flexibility measurement was performed with sit and reach flexibility test. Artistic gymnastics-specific jump movement was evaluated looking at the angle between lower extremities using the Dartfish motion analysis program. Baseline measurements taken before the standard warm-up and the measurements taken after static stretching were assessed. Four sets of gymnastics moves each lasting two minutes were performed. The tests were repeated after each set. Static stretching was found to affect vertical jump performance significantly. Significant differences were found between Jump2 and Jump1 (p=0.01), Jump2 and Jump3 (p=0.03), Jump2 and Jump4 (p=0.01), Jump2 and Jumop5 (p=0.004), and Jump2 and Jump6 (p=0.009). In flexibility-related changes, significant differences were found between Reach2 and Reach3 (p=0.03), and Reach2 and Reach6 (p=0.006). Static stretching was found to have no significant effect on the lower extremity straddle jump degree. In conclusion, although the static stretching protocol reduced vertical jump performance significantly, it did not affect the artistic gymnastics-specific jump move. The negative effects of static stretching on jump height approached the baseline value approximately 4 minutes later.